DESIGN AND DEVELOPMENT OF AN AUTOMATION AND PUMP TIMER SYSTEM FOR AEROPONICS - Salamun Trisna Nurohhim; Arman Meiranda; Nina Paramytha Is (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to design an automation and timer system for aeroponic pumps in the cultivation of currant tomatoes (Solanum pimpinellifolium) to improve energy efficiency and optimize nutrient delivery. The system was designed using an Arduino Nano microcontroller integrated with the RTC DS3231 module as a pump operational time controller, TDS Meter sensor to monitor dissolved nutrient concentration, and pH Meter sensor to measure nutrient solution acidity level. Testing was conducted for 14 days to evaluate sensor performance in responding to predetermined setpoints. The results showed that the implementation of the timer system resulted in energy savings of 83% compared to the system without a timer, where energy consumption decreased from 11.62 kWh to 1.93 kWh per day. TDS Meter and pH Meter sensors were able to consistently monitor nutrient parameters with values approaching optimal setpoints. The RTC DS3231 module functioned optimally in controlling the pump operational cycle without experiencing time reading errors. The designed system proved effective in improving energy efficiency and maintaining stable plant growth environment conditions, making it suitable for implementation as an automation-based aeroponic system.